THE PRESENTATION OF THE GRASSHOPPER TEG OF AN ANT TO THE SULTAN: THE QASIDE-I HAMIDIYYE OF TAYYIB-ZADE HAFIZ MEHMED ZUHDI EFENDI (b. 1270/1853-1854 - d. 1332/1914) - Top, Yılmaz (Marmara Üniversitesi, 2025)
Tayyib-zâde Hâfız Mehmed Zühdî Efendi, a scholar, teacher, hafiz, prose writer and poet, is a figure who grew up in Trabzon, one of the important science and culture centers of the 19th century. This study aims to introduce the 82-couplet Qasida-i Hamidiyye, which we believe Mehmed Zühdi Efendi completed/presented to the sultanate approximately on 14 June 1900. The subjects that Zühdi Efendi addresses in the petition section of Qasida-i Hamidiyye make visible the issues that he presents his expectations to Sultan Abdulhamid II through this poem and requests mercy and justice from the sultanate. It would not be wrong to place Qasida-i Hamidiyye among the class of qasidas that largely continue the classical qasida tradition in all its aspects in form and in content, on the condition that it accepts its strong contact with the concrete data of real life. The dismissal of Zühdî Efendi, which probably occurred between the second half of 1316/1898-1899 and 1317/1899-1900, has enabled the acquisition of new information about the life of the poet of Qasida-i Hamidiyye, which has not been included in biographical sources, through the circumstances that led to this incident and the circumstances that brought about it.

Âlim, muallim, hâfız, nâsir ve şair Tayyib-zâde Hâfız Mehmed Zühdî Efendi, 19. yüzyılın önemli ilim ve kültür merkezlerinden biri olan Trabzon’da yetişmiş bir şahsiyettir. Bu çalışmada, Mehmed Zühdî Efendi’nin tahminen 16 Safer 1318/14 Haziran 1900 tarihinde tamamladığı/saltanat makamına sunduğu düşünülen 82 beyitlik Kasîde-i Hamîdiyye’sinin tanıtılması amaçlanmaktadır. Zühdî Efendi’nin Kasîde-i Hamîdiyye’nin arzuhâl bölümünde ele aldığı mevzular, onun bu şiir vasıtasıyla Sultan II. Abdülhamîd’e beklentilerini sunmaya ve saltanat makamından merhamet ve adalet talep etmeye konu olan hususları görünür kılmaktadır. Kasîde-i Hamîdiyye’yi, klasik kaside geleneğini şekilde her yönüyle, içerikte ise gerçek hayatın somut verileriyle kuvvetli temasını kabul etmek koşuluyla büyük ölçüde devam ettiren kasideler sınıfına yerleştirmek yanlış olmaz. Zühdî Efendi’nin, muhtemelen 1316/1898-1899 yılının ikinci yarısı ile 1317/1899-1900 yılı içerisindeki bir tarih arasında maruz kaldığı görevden alınma hadisesi, bu hadiseyi hazırlayan ve bu hadisenin meydana getirdiği koşullar üzerinden Kasîde-i Hamîdiyye şairinin hayatına dair, biyografik kaynaklara konu olmamış yeni bilgilerin elde edilmesini sağlamıştır.
KARINCADAN SULTAN’A ÇEKİRGE BUDU SUNUMU: TAYYİB-ZÂDE HÂFIZ MEHMED ZÜHDÎ EFENDİ’NİN (doğ. 1270/1853-1854 - öl. 1332/1914) KASÎDE-İ HAMÎDİYYE’Sİ
Keywords: Classical Turkish Literature of Ottoman Field; Osmanlı Sahası Klasik Türk Edebiyatı